Sämtliche Werke - Kleist, Ewald Christian von 1715-1759 (Berlin Voss, 1766)
His poem 'Spring' (1749) and Anacreontic poetry made Ewald Christian von Kleist (1715-1759) famous and popular in his time. The law student was an officer by profession; he had been in Danish service since 1736 before joining the Prussian army in 1740 and taking part in Frederick II's wars. He died in Frankfurt a.d. Oder as a result of a wound suffered in the Battle of Kunersdrof.
Contains the Trauerspiel 'Seneka', next to the poem 'Der Frühling'
A Viennese edition of this work from 1765 was in Mozart's personal library. The original Berlin edition was edited by Karl Wilhelm Ramler.
Ex libris W. Grempel, Berlin (Stamp)
Keywords: 18th Century (1701-1800); Poetry; Play (theater); Prussia (Germany)